If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -4x + 6 = 5 Reorder the terms: 6 + 3x + -4x = 5 Combine like terms: 3x + -4x = -1x 6 + -1x = 5 Solving 6 + -1x = 5 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -1x = 5 + -6 Combine like terms: 6 + -6 = 0 0 + -1x = 5 + -6 -1x = 5 + -6 Combine like terms: 5 + -6 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1
| k/16=0 | | 4x+y+130=0 | | r/17=-3 | | 0=3v^2-81 | | u^2+3=43 | | 5.00-3.50= | | 96=2x^2+8 | | X=3/(3/20) | | n+(-17)=-36 | | a-b+c=7 | | x*0.04=1100 | | 5x+-2=11 | | ×/15=20/30 | | 2(9x+11)=2(4x+6) | | 7x-3x-10=34 | | 3x+7+2x+3=60 | | 13n=-13 | | 4x+4y=8x-2y | | 22x+1=4 | | 10+m=-6 | | b+16=13 | | 4x-8=7-6 | | 8a+2y-3a+7= | | 3[x+3]-2[x-1]=5[x-5] | | 6x=y-3 | | 3y=5x-16 | | H^2-36+5h=0 | | 16x^2-68x+16= | | 6x-3x^2=1600 | | 0.7n+3=4 | | 16x^2-22x+16= | | 2x^2+10x-875=0 |